Environmental treatment and remediation using h-BN based smart and hybrid membrane. (October 2022) - Salahuddin, Zarrar; Farrukh, Sarah; Jan, Rahim; Ayub, Atif; Hussain, Arshad; Pontié, Maxime; Ahmed, Anas; Mubashir, Muhammad
Abstract: Corrosion is a major problem resulting from acid gases found in natural gas being transported in pipelines. To solve this problem, high aspect ratio h-BN nanosheets have been incorporated and are properly assimilated in the CA matrix, this led to an increase in tortuous path of flow for the gas resulting in smooth, dense membrane samples causing exceptional permeability reduction. Hexagonal Boron Nitride (h-BN) nanosheets have been synthesized and incorporated into cellulose acetate (CA) matrix using solution casting method. Nanosheets of various sizes, separated by varying centrifugation speeds (i.e. 500 rpm, 700 rpm, 1500 rpm, 2000 rpm and 2500 rpm), have been prepared and used for our work. The resulting nanocomposites, having thickness ranging between 40 and 60 μm, were then tested for CO2 gas permeability reduction using both short-term (8 h) tests as well as long-term (72-h tests). As a result of these tests, a maximum CO2 permeability reduction of 99.84% is found with a minimum CO2 permeability of 3.25 barrer. For dimensional analysis of both nanosheets and nanocomposites, scanning electron microscopy (SEM) analysis is used. For verifying the presence of the required functional groups in our synthesized samples, FT-IR spectroscopy is used. Moreover, to confirm the presence of crystalline phases, X-ray Diffraction (XRD) analysis is used. Also, tensile testing is used to analyze the mechanical robustness and it was found that nanocomposite samples exhibited higher tensile strength as compared to pristine samples. Furthermore, tribological property analysis was also carried out for adhesion testing of polymeric material with steel. Graphical abstract: Image 1 Highlights: Smart h-BN based polymer membranes were synthesized. Maximum CO2 gas barrier performance of 99.84% was achieved. Excellent adhesion of membrane with mild carbon steel was observed. Environmental remediation was performed using resultant membrane.